Poster 251: Autograft Associated with Lower Risk of Repeat Revision Anterior Cruciate Ligament Reconstruction than Allograft: Results from a Large Integrated Healthcare System. Issue 7 (30th July 2022) - Chang, Richard; Royse, Kathryn; Burfeind, William; Ding, David; Maletis, Gregory; Heffner, Michael
Objectives: With the rising utilization of primary anterior cruciate ligament reconstruction (ACLR), the burden of revision ACLR (rACLR) has also increased. Graft choice for rACLR is complicated by patient factors and the remaining available graft options. This study examines the relationship between graft type at the time of rACLR and the risk of repeat rACLR (rrACLR). Methods: We conducted a cohort study from a US integrated healthcare system's ACLR registry. The study population included patients with a primary isolated ACLR, between 2005-2020, who then went on to have an aseptic rACLR. Graft type used at revision surgery, classified as autograft versus allograft, was the exposure of interest. Multivariable Cox proportional hazard regression was used to evaluate the risk of aseptic rrACLR with ipsilateral and contralateral reoperation as secondary outcomes. Models included factors at the time of the revision procedure (age, gender, body mass index, smoking status, staged revision, femoral fixation, tibial fixation, femoral tunnel method, lateral meniscus injury, medial meniscus injury, and cartilage injury) and a factor from the primary ACLR (activity at injury) as covariates. Results: 1747 rACLR procedures were included. The crude cumulative aseptic rrACLR incidence at 8-years follow-up was 13.9% for allograft and 6.0% for autografts (Figure 1 ). Cumulative ipsilateral reoperation incidence at 8-years follow-up was 18.3% for allograft and 18.9% for autograft; contralateral reoperation cumulative incidence was 4.3% for allograft and 6.8% for autograft. With adjustment for covariates, a lower aseptic rrACLR risk was observed for autografts compared with allografts (HR=0.30, 95% CI=0.18-0.50, p <0.0001). No differences were observed for ipsilateral reoperation (HR=1.05, 95% CI=0.73-1.51, p=0.78) nor for contralateral reoperation (HR=1.33, 0.60-2.97, p=0.48) for autografts compared with allografts. Conclusions: The use of autograft at rACLR was associated with a 70% reduced risk of rrACLR compared to allograft in this large integrated health care system registry. When accounting for all reoperations after rACLR, we found no significant difference in risk between autograft and allograft. In order to minimize the risk of rrACLR, surgeons should consider using autograft for rACLR when possible. Figure 1. Cumulative Incidence of Asceptic Re-revision by Graft Type.